FEATURES OF STOMACH ULCERS IN CHILDREN - Ibatova Sh. M.; Sharipov U. M. (American Journals Publishing, 2023)
Gastric ulcer in children is a chronic disease in which the mucous tissue of the gastric walls is damaged. The pathology occurs in isolation or with the involvement of the duodenum and other structures of the gastrointestinal tract (GIT) in the pathological process [1,3,5,7]. Children of middle and high school age suffering from chronic gastritis, duodenitis and other long-term lesions of the digestive system are most susceptible to this form of the disease.